Ar-Flood Detector - Laing, Leonell Avun; Ishak, Maizul (Progress in Engineering Application and Technology, 2023)
One of the most dangerous natural disasters is flooding since it gravely compromises agriculture, infrastructure, and human lives. Communities in low-lying areas are more vulnerable to flooding-related losses. The purpose of this project is to develop a flood detection system that can detect early signs of floods in low-lying areas using Arduino UNO. The system was powered using a solar panel. The three water sensors were used as inputs for the system as the sensors detect the presence of water at three different levels. GSM module was an essential component that is used for notifying the user regarding the levels of water. A buzzer has also been installed as an alarm to warn users when the water reaches a dangerous level. With a system that can detect flood and alerting in real-time, may minimize the damage from flood disaster and prevent loss of life.